Differences in Dental Implant Survival between Immediate vs. Delayed Placement: A Systematic Review and Meta-Analysis - Rishi Patel; Cemal Ucer; Simon Wright; Rabia S. Khan (MDPI AG, 2023)
Objectives: To compare the impact of immediate and delayed implant placement upon the survival of implants and to investigate the differences in implant survival between immediate and delayed placement in adults. Methods: A search for the relevant literature was performed using the databases of CENTRAL, MEDLINE and Scopus. The studies found were limited to publications between 2014 and 2022, written in the English language, peer-reviewed, and were randomised trials or comparative studies. The quality of the evidence was assessed using the Cochrane Risk of Bias 2.0 and Risk of Bias in Non-randomised Studies-of Interventions appraisal tools and implant survival, and the primary outcome was meta-analysed using RevMan v.5.3. Results: A total of 10 studies were eligible for inclusion, including six randomised controlled trials and four non-randomised comparative studies. Five of the six randomised trials observed a low risk of bias, while the comparative studies had a moderate-to-serious risk of bias. The search strategy resulted in 341 implants placed immediately into fresh extraction sites (332 survived, 97.4%) and 359 implants inserted into delayed sites (350 survived, 97.5%). Conclusion: The meta-analysis demonstrated that there was no significant difference in the implant survival rates between immediately placed implants and implants placed using a delayed timing protocol (risk ratio 0.99; 95% CI 0.96, 1.02, Z = 0.75, p = 0.45). However, the detailed analysis showed that slightly more implant failures happened in the immediate dental implant placement group, with survival rates in some studies ranging between 90 and 95%, while the delayed placement group had survival rates of more than 95%.